Agile Engineering: Introduction of a new Management Concept - Arthur Kolb; Philipp Hecker (Journal of Applied Leadership and Management, 2016)
Is it feasible to apply Agile Project Management methods known from the area of software development to general and project management tasks in engineering? Doing so, is it possible to increase employee motivation and engagement?
Keywords: 650; Agile Engineering; Management Concept; agile procet management; software development